Pemberdayaan Masyarakat Melalui Program Masjid Literasi “Rumah Literasiku” - Uswatun Hasanah (Jurnal Medika: Medika, 2025)
This report of community service (PkM) discusses community service in the form of a library facility namely "Rumah Literasiku" through the literacy mosque program, at the Baiturrahman Mosque, Brumbung Hamlet, West Pakandangan Village, Bluto, Sumenep. The aim of this service is to increase the literacy interest of the local community, and make the community literate, so that they can change their mindset and instill a strong mindset about the importance of education, as well as to increase the community's insight to be more advanced, supporting education. The service method used in PkM is Asset Based Community Development (ABCD), a community service approach carried out by empowering the community, namely searching for assets that originate from community strengths. Based on the description provided in this community service report, it can be concluded that community service is carried out through coaching the Brumbung Pakandangan Barat community. The program takes the form of establishing a literacy house at the Baiturrahman Brumbung Pakandangan Barat Mosque, Bluto, Sumenep. This program was continued by partner stakeholders from the management of the Arrahman Foundation. There is a change in the impact of school children who are starting to like visiting the literacy home library.